2013
DOI: 10.1136/bmjopen-2013-002733
|View full text |Cite
|
Sign up to set email alerts
|

Parental comprehension of the benefits/risks of first-line randomised clinical trials in children with solid tumours: a two-stage cross-sectional interview study

Abstract: ObjectivesTo analyse the parental understanding of informed consent information in first-line randomised clinical trials (RCTs) including children with malignant solid tumours and to assess parents’ needs for decision-making.DesignObservational prospective study.Setting3 paediatric oncology centres in the Parisian region in France.Participants53 parents were approached to participate in a RCT for their child with malignant solid tumour, over a 1-year period. 40 parents have been interviewed in our study.Primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 32 publications
(23 reference statements)
1
24
0
Order By: Relevance
“…Despite good communication, accurate understanding is difficult to obtain in daily practice due to various obstacles, 32 mainly emotional and psychosocial factors, [37][38][39] clinical technicalities or study design. 29,35,40 Authors outline categories ("therapeutic misconception", "therapeutic misestimation", "unrealistic optimism") to discriminate a serious misunderstanding making consent invalid from attitudes merely reflecting preferences (risk aversion) or mindset (hope, optimism). 28,33,41 Urgency to decide soon after diagnosis is a known aggravating factor, 27,42 even if randomisation -a research aspect which is difficult to understand -is planned at distance from inclusion (three months in Alberto's case).…”
Section: Consentmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite good communication, accurate understanding is difficult to obtain in daily practice due to various obstacles, 32 mainly emotional and psychosocial factors, [37][38][39] clinical technicalities or study design. 29,35,40 Authors outline categories ("therapeutic misconception", "therapeutic misestimation", "unrealistic optimism") to discriminate a serious misunderstanding making consent invalid from attitudes merely reflecting preferences (risk aversion) or mindset (hope, optimism). 28,33,41 Urgency to decide soon after diagnosis is a known aggravating factor, 27,42 even if randomisation -a research aspect which is difficult to understand -is planned at distance from inclusion (three months in Alberto's case).…”
Section: Consentmentioning
confidence: 99%
“…Likewise, research participation is often experienced as a choice out of necessity. 1,26,31,35,40,43,45 Phase 1 trials, often seen as last chance for controlling the disease, and correlative biological studies 23 raise particular issues in this regard; for instance, it is argued that families should be offered the choice to opt for trial participation while refusing correlative (non-beneficial) studies. 46 Hence, offering research participation can have clinical and personal impact, both on patients and parents, either positive (better follow-up, improved self-image or sense of control, "a glimmer of hope") 21,36,[47][48][49] or negative (health insurance coverage, anxiety or remorse, medical futility or broken alliance).…”
Section: Consentmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown how qualitative research can inform trial development in challenging settings, including the identification of barriers and potential solutions to successful recruitment21–23 and acceptability of approaches to consent procedures 24 25. Historically, there has been a paucity of such research, despite its potential to help trialists understand the complexities and challenges arising from the social contexts in which trials are based 26. A recent systematic mapping review of qualitative research in the clinical trials setting indicated27 that while such work had considerable potential to inform trials, this potential is often lost because the qualitative study findings are too late to inform the partner trials.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Decision makers might not fully understand trial characteristics; however, some study characteristics like randomization procedures and the use of placebos might negatively affect consent in clinical trials. [8][9][10][11] Study characteristics' effects on consent rates in neonatal clinical trials have not been reported.…”
mentioning
confidence: 99%